Maleic anhydride polypropylene modified cellulose nanofibril polypropylene nanocomposites with enhanced impact strength. Issue 3 (15th September 2014) - Peng, Yucheng; Gallegos, Sergio A.; Gardner, Douglas J.; Han, Yousoo; Cai, Zhiyong
Abstract : Development of cellulose nanofibrils (CNFs) reinforced polypropylene (PP) nanocomposites using melt compounding processes has received considerable attention. The main challenges are to obtain well‐dispersed CNFs in the polymer matrix and to establish compatible linkages between the CNFs and PP. Manufacturing of CNF reinforced PP nanocomposites was conducted using a twin‐screw co‐rotating extruder with the masterbatch concept. Modifications of CNFs using maleic anhydride polypropylene were performed. The best mechanical properties of the nanocomposites are 1.94 GPa (tensile modulus), 32.8 MPa (tensile strength), 1.63 GPa (flexural modulus), 50.1 MPa (flexural strength), and 3.8 kJ m −2 (impact strength), which represents about 36, 11, 21, 7, and 23% improvement, respectively, compared to those of pure PP (1.43 GPa, 29.5 MPa, 1.35 GPa, 46.9 MPa, and 3.1 kJ m −2 ). Fracture morphology examination indicated good dispersion of CNFs in the PP matrix was achieved through this specific manufacturing process. MAPP treatments enhanced the interfacial adhesion between the CNFs and PP. POLYM. COMPOS., 37:782–793, 2016. © 2014 Society of Plastics Engineers